Marinyo as a medium of traditional communication in the digital era: hybridization, opinion leadership, and cultural sustainability in Ambonese society - Latuheru, Rido; Bahfiarti, Tuti; Sonni, Alem Febri (Frontiers in Communication, 2025)
This study examines the transformation of Marinyo, a traditional communication institution in Ambonese society, within the context of digital media expansion and the transition from Industry 4.0 to Society 5.0. The research addresses the critical challenge of maintaining cultural communication systems while embracing technological advancement, a concern highlighted by UNESCO’s directives on cultural preservation. Using ethnographic communication methods and in-depth interviews conducted across multiple indigenous communities representing both Christian and Muslim populations in Ambon, Indonesia, this research analyzes how Marinyo adapts as a traditional opinion leader in contemporary information ecosystems. The study aims to understand the hybridization processes, legitimacy transformation, and cultural sustainability of traditional communication institutions in the digital age. Findings reveal that rather than being replaced by digital technologies, Marinyo undergoes a complex hybridization process, evolving into unique communication formations that blend traditional authority with digital competencies. The study identifies two distinct hybridization patterns: a Divergent Hybridization Model, characterized by functional bifurcation between administrative-digital and ceremonial-traditional channels, and a Convergent Hybridization Model, marked by organic integration of traditional and digital elements. Results demonstrate how the cultural legitimacy of Marinyo remains a decisive factor in maintaining influence amid digital media penetration, while legitimacy sources expand to include technical competence and formal institutional recognition. This research contributes to understanding traditional communication systems’ resilience and cultural sustainability in the digital age, offering theoretical and practical implications for developing culturally responsive communication policies that bridge digital divides while preserving cultural identity. The novelty of this research lies in its comprehensive analysis of communication hybridization in indigenous contexts, extending beyond Western-centric media theories to provide insights into how traditional institutions strategically negotiate global technological forces while maintaining cultural authenticity.